2022
DOI: 10.3390/antiox11030499
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean Diet Has a Protective Role against Metabolic and DNA Damage Markers in Colorectal Cancer Patients

Abstract: Oxidative stress (OS) and inflammation have been related to colorectal cancer (CRC), but the influence of the Mediterranean diet (MD) on these parameters is unknown. Therefore, the aim of this study was to determine the association between adherence to the MD and markers of OS and DNA damage in CRC patients and to study the influence of adherence to the MD on metabolic and tumor-related factors. This prospective observational study included a total of 80 patients diagnosed with CRC. Adherence to the MD was est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
0
7
0
3
Order By: Relevance
“…In general, levels of antioxidative enzymes are lower in cancer, while 8-oxodG levels are higher [ 33 ]. Moreover, adherence to a Mediterranean diet has been associated with decreased levels of 8-oxodG in CRC [ 34 ], while synbiotic foods—which include prebiotics and probiotics, a combination of live bacteria and mostly carbohydrate-based substances, such as dietary fiber or starch—have been shown to promote the activity of beneficial bacteria in the gut. In this sense, perioperative administration of probiotics/synbiotics may help to decrease postoperative complications in CRC patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, levels of antioxidative enzymes are lower in cancer, while 8-oxodG levels are higher [ 33 ]. Moreover, adherence to a Mediterranean diet has been associated with decreased levels of 8-oxodG in CRC [ 34 ], while synbiotic foods—which include prebiotics and probiotics, a combination of live bacteria and mostly carbohydrate-based substances, such as dietary fiber or starch—have been shown to promote the activity of beneficial bacteria in the gut. In this sense, perioperative administration of probiotics/synbiotics may help to decrease postoperative complications in CRC patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several nutrients of the Mediterranean diet can modify the epigenome (which regulates the modulation of gene expression as studied by nutrigenomics), inhibiting the development of tumors and acting as protective factors [ 28 ]; this effect can be partly explained by the ability to support an effective repair of DNA damage, modulating the activity of histones and RNA methyl marker [ 29 ]. A high adherence to the Mediterranean diet has a protective role against metabolic and oxidative DNA damage, improving the antioxidant system, as demonstrated by the reduced levels of oxo-708-dihydro-20-deoxyguanosine and the increase in those of HDL-cholesterol and glutathione peroxidase [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of Mediterranean diet in tumor prevention is then well established; however, less is known about the role of diet in tumor progression in patients with an already established diagnosis of neoplasm [ 38 ]. In this regard, in a prospective study of 80 patients affected by colorectal cancer, Acevedo et al found that high adherence to the Mediterranean diet was associated with less severe histological degrees and lower presence of synchronous adenomas [ 30 ]. Moreover, in the Multiethnic Cohort Study were enrolled 6370 patients, finding a better aMED scores associated with lower risks of mortality and cancer [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Acevedo-León, MD increased the level of glutathione peroxidase. Additionally, this diet decreased 8-oxoDG (8-oxo-7′8-dihydro-2′-deoxyguanosine), which is one of the oxidized DNA bases in colorectal cancer patients [ 131 ]. Additionally, the Mediterranean diet contains many components that reduce the risk of colorectal cancer, e.g., fruits and vegetables, which contain fiber that protects against colorectal cancer [ 132 ].…”
Section: Diet and Colorectal Cancermentioning
confidence: 99%